YBC: a stellar bolometric corrections database with variable extinction coefficients: Application to PARSEC isochrones - Chen, Yang; Girardi, Léo; Fu, Xiaoting; Bressan, Alessandro; Aringer, Bernhard; Dal Tio, Piero; Pastorelli, Giada; Marigo, Paola; Costa, Guglielmo; Zhang, Xing (Astronomy and astrophysics (Berlin), 2019)
We present the YBC database of stellar bolometric corrections, in which we homogenise widely used theoretical stellar spectral libraries and provide BCs for many popular photometric systems, including Gaia filters. The database can easily be extended to additional photometric systems and stellar spectral libraries. The web interface allows users to transform their catalogue of theoretical stellar parameters into magnitudes and colours of selected filter sets. The BC tables can be downloaded or implemented into large simulation projects using the interpolation code provided with the database. We computed extinction coefficients on a star-by-star basis, hence taking into account the effects of spectral type and non-linearity dependency on the total extinction. We illustrate the use of these BCs in PARSEC isochrones. We show that using spectral-type dependent extinction coefficients is necessary for Gaia filters whenever A V ≳ 0.5 mag. Bolometric correction tables for rotating stars and tables of limb-darkening coefficients are also provided.